The contribution of parental acceptance of hearing parents and communicatin modes in semantic language ability on deaf children - Victoria Geraldin Wahyudi Ongkowardoyo; Frieda Maryam Mangunsong (Universitas Negeri Yogyakarta, 2021)
Many deaf children are born to hearing parents, therefore deaf children will naturally have different communication modes with their parents. This condition is difficult for parents to accept their children because children will use sign language while parents will speak orally. This different mode also causes delays in semantic language development. The use of appropriate communication modes (Independent Variable – IV1) and parental acceptance (IV2) was found to contribute to semantic language development (Dependent Variable - DV). So far, no research has yet been found that examines those variables on deaf children in Indonesia. Therefore, this study will look at the contribution of parental acceptance and communication modes on the semantic language development of deaf children. Participants are deaf children and their parents. In the analysis using multiple linear regression, found that both IVs did not affect DV. Furthermore, will be discussing other factors surrounding the three variables involved that can explain the result.